GAMBARAN POLA MAKAN PADA PASIEN HIPERTENSI DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2023 - Syukur J. Gulo; Tesalonika Br Ginting, (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Diet is one of the efforts in overcoming hypertension sufferers so they can control their habits by adjusting the amount of food, type of food, meal schedule and balance nutritional intake. A balanced menu needs to be started and well known so that controllable eating habits will be formed. Hypertension is a non-communicable disease that can cause blood pressure to increase where systolic and diastolic are above normal limits. Factors that can cause hypertension are genetic factors (heredity), gender, age. The aim of the study is to find out the eating patterns of hypertensive patients. The research uses a quantitative method where data collection is carried out using a questionnaire of 25 questions so as to be able to dig deeper into the diet of hypertensive patients. The sampling technique uses random sampling of 53 respondents. The data analysis technique uses is descriptive. The results of the study are: eating patterns of hypertensive patients based on the amount of food in good category 45 respondents (84.9%). The eating pattern of hypertensive patients based on the type of food is in good category, 43 respondents (81.1%). The eating pattern of hypertensive patients based on the frequency of eating was in good category, 44 respondents (83.0%). Researcher's suggestion: It can be used as a recommendation for one of the non-pharmacological management of hypertensive patients by providing health education about diet, and used as information to maintain eating patterns in hypertensive patients.